Exposure to low UVA doses increases KatA and KatB catalase activities, and confers cross-protection against subsequent oxidative injuries in pseudomonas aeruginosa - Pezzoni, Magdalena (2016)
Solar UVA radiation is one of the main environmental stress factors for Pseudomonas aeruginosa. Exposure to high UVA doses produces lethal effects by the action of the reactive oxygen species (ROS) it generates. P. aeruginosa has several enzymes, including KatA and KatB catalases, which provide detoxification of ROS. We have previously demonstrated that KatA is essential in defending P. aeruginosa against high UVA doses. In order to analyse the mechanisms involved in the adaptation of this micro-organism to UVA, we investigated the effect of exposure to low UVA doses on KatA and KatB activities, and the physiological consequences. Exposure to UVA induced total catalase activity; assays with non-denaturing polyacrylamide gels showed that both KatA and KatB activities were increased by radiation. This regulation occurred at the transcriptional level and depended, at least partly, on the increase in H2O2 levels. We demonstrated that exposure to low UVA produced a protective effect against subsequent lethal doses of UVA, sodium hypochlorite and H2O2. Protection against lethal UVA depends on katA, whilst protection against sodium hypochlorite depends on katB, demonstrating that different mechanisms are involved in the defence against these oxidative agents, although both genes can be involved in the global cellular response. Conversely, protection against lethal doses of H2O2 could depend on induction of both genes and/or (an)other defensive factor(s). A better understanding of the adaptive response of P. aeruginosa to UVA is relevant from an ecological standpoint and for improving disinfection strategies that employ UVA or solar irradiation.